Elemental Gains and Losses during Hydrothermal Alteration in Awak Mas Gold Deposit, Sulawesi Island, Indonesia: Constraints from Balanced Mineral Reactions - Ernowo, Ernowo (MDPI, 2022)
Hydrothermal gold mineralization is commonly associated with metasomatic processes resulting from interaction of hostrock with infiltrating hot aqueous fluids. Understanding of the alteration mechanism requires quantification of element changes in altered rock, relative to the unaltered or least-altered rock, representing the protolith. Balanced mineral reactions are used to gain quantitative insight into the alteration process associated with gold mineralization at the Awak Mas deposit. Three representative samples were carefully selected from the least-altered pyllite and the two alteration zones bordering the mineralization. Mineral mode, textural features, and mineral compositions were studied by microscopy and electron microprobe analyzer (EMPA). Quantitative modal analysis was performed with a Quanta 650 F QEMSCAN® system. The hydrothermal alteration sequence around the mineralization starts with the proximal albite–ankerite–pyrite alteration zone via the distal albite–chlorite alteration zone to the least-altered phyllite wall-rock. Balanced mineral reaction calculations were performed to evaluate elemental gains and losses. Most noticeable is the addition of Si, Na and Ca to each alteration zone. This alteration is represented by the almost complete replacement of muscovite by albite. The addition of Fe and S was highest in the albite–ankerite–pyrite alteration zone. Alteration of the least altered phyllite to the albite–chlorite zone involved a mass increase of 14.5% and a neglectable volume increase of 0.6%. The mass and a volume increase from the least altered phyllite to the albite–ankerite–pyrite zone was 40.5% and 0.47%, respectively. The very low volume change during alteration is also corroborated by the textural preservation indicating isovolumetric metasomatic reactions. The replacement of muscovite by albite may have had an important effect on the change of the rock failure mode from ductile to brittle, with consequences for the focusing of fluid flow.